The assessment of the effects of Batho Pele Principles on public service delivery in the Department of Sport, Arts and Culture - Mabunda, Jennifer (My University, 2013)
Refer to document
Thesis (MPA.) -- University of Limpopo, 2013
Keywords: Batho pele principles; Public services delivery; Department of Sport, Arts and Culture; Public Administration; Public Services